Seismic risk assessment of low rise RC frame structure. (February 2016) - Melani, A.; Khare, R.K.; Dhakal, R.P.; Mander, J.B.
Abstract: Seismic evaluation and financial risk analysis of typical low rise reinforced concrete frames are performed. The financial risk assessment is determined on the basis of results of incremental dynamic analysis (IDA) of reinforced concrete frames analyzed using nonlinear time history analyses on IDARC platform with a suite of 20 ground motion records used by Vamvatsikos and Cornell (2002) for mid-rise buildings. Three frames were analyzed with capacity design concepts taking into account shear capacity, flexural capacity and contribution from floor reinforcement to beams. Maximum inter-story drift ratios obtained from time-history analyses are plotted against ground motion intensities. Results are statistically interpreted to develop cumulative distribution functions for frames. Fragility curves are plotted for HAZUS damage states of conventional structures. Fragility curves thus drawn are used to estimate the expected annual loss (EAL) of low rise RC frames using quadruple integral formula based on probabilistic financial risk assessment framework.